2018
DOI: 10.1111/bjh.15548
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal COX2‐PG secretome engages NR4A‐WNT signalling axis in haematopoietic progenitors to suppress anti‐leukaemia immunity

Abstract: The bone marrow (BM) microenvironment (niche) plays important roles in supporting normal/abnormal haematopoiesis. We investigated the interaction between leukaemic mesenchymal niche and haematopoietic stem and progenitor cells (HSPCs) using the model of Fanconi anaemia (FA), a genetic disorder characterized by BM failure and leukaemia. Healthy donor HSPCs co-cultured on mesenchymal stromal cells (MSCs) derived from FA patients with acute myeloid leukaemia (AML) exhibited higher human engraftment and myeloid ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…As one of the predicted targets of TW for the treatment of AML, PTGS2 can be acted by 7 active compounds in TW. It has been reported that it can selectively inhibit cox-2 and play a role in the treatment of AML (36)(37)(38) . This means that multiple active ingredients in traditional Chinese medicine can act on a single target to take effect in the treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the predicted targets of TW for the treatment of AML, PTGS2 can be acted by 7 active compounds in TW. It has been reported that it can selectively inhibit cox-2 and play a role in the treatment of AML (36)(37)(38) . This means that multiple active ingredients in traditional Chinese medicine can act on a single target to take effect in the treatment of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that Tripterygium wilfordii may have multiple active ingredients through multiple pathways to prevent and treat AML. Such as Toll-like receptor signaling pathway, as a part of the innate immune system, studies have shown that various hematological malignant cells, including AML cells, express TLRs, and TLR agonists may directiy effect on the leukemic cells (38) . Due to the indirect anti-leukemia effect caused by the activation / stimulation of normal immuneocompetent cells, such as eradicating residual leukemia cells after induction therapy, TLR is considered a possible drug target in AML (42) .…”
Section: Discussionmentioning
confidence: 99%
“…In a study on the interaction between hematopoietic stem and progenitor cells (HSPCs) and leukaemia mesenchymal niche, mesenchymal stromal cells (MSCs) derived from Fanconi anaemia (FA) patients with acute myeloid leukaemia (AML) (FA-AML MSCs) promoted expansion of healthy donor HSPCs, myeloid expansion of bone marrow CD34 + cells, and Treg differentiation. The HSPC/myeloid expansion is mediated by leukemic mesenchymal COX-2-prostaglandin (PG) secretome [ 85 ]. Three pathways have been identified that mediate the effect of the COX-2 PG secretome: (i) NR4A2 signaling, (ii) Wnt signaling, and (iii) Treg function pathways.…”
Section: Nurr1 and Inhibition Of Antitumor Immunitymentioning
confidence: 99%
“…Downregulation of PG by COX-2 inhibition ameliorates HSPC/myeloid expansions and reduces expression of NR4A and expression of Treg genes (Foxp3 and CTLA-4) in AML MSCs cocultured with CD34 + populations, indicating an association between the COX2-PG secretome and NR4A-Treg signaling [ 85 ]. In addition, Nurr1 and Nur77 act synergistically on the promoter of proto-oncogene β-catenin (CTNNB1) to enhance Wnt activation [ 85 ]. CTNNB1 knockdown significantly upregulates CD8 + CCR7 + T effector cells, an important subset in anti-leukemia immunity, without affecting the Treg population.…”
Section: Nurr1 and Inhibition Of Antitumor Immunitymentioning
confidence: 99%
“…Therefore, despite advancements in our understanding of the molecular and genetic alterations in AML, the abnormalities in BM-MSCs derived from AML patients (AML-MSCs) have not been fully elucidated. AML-MSCs overexpress several chemokines and cytokines, such as stromal cell-derived factor-1 (SDF-1, also known as CXCL12) 9 , prostaglandins (PGs) 10 , galectin 3 11 , apoptosis repressor with caspase recruitment domain (ARC) protein 12 , and IL-10 13 and were more prefer to support LC survival compared with normal MSCs. Proteomic profiling has also revealed a different protein expression profile of AML-MSCs, and certain MSC protein expression signatures may be related to patient survival and remission 11 .…”
Section: Introductionmentioning
confidence: 99%